Enhancing Student Collaboration in Science Education Through Outdoor Learning Transformation: Meningkatkan Kolaborasi Siswa dalam Pendidikan Sains Melalui Transformasi Pembelajaran di Luar Kelas - Khoirot, Mil’Al; Setiyawati, Enik (Indonesian Journal of Innovation Studies, 2024)
This study explores the efficacy of implementing outdoor learning to enhance student collaboration in fourth-grade science education at SD Muhammadiyah 1 Candi Sidoarjo, addressing a gap in research regarding its application in primary school science education. Using a descriptive qualitative approach with observation, interviews, and documentation, data analysis followed the Miles and Huberman model. Results indicate successful implementation of outdoor learning, fostering collaboration among students, particularly in accepting responsibility, assisting peers, and respecting opinions. Variations in collaboration effectiveness were noted between student groups. Findings suggest that carefully planned outdoor learning activities can create an engaging learning environment, improving student collaboration and overall learning outcomes in primary school science education. Highlight: Outdoor learning in primary science: Enhancing student collaboration and engagement. Qualitative approach: Investigating student perspectives on outdoor education. Effective peer interactions: Fostering teamwork in outdoor learning environments. Keyword: Outdoor learning, Student collaboration, Primary school, Science education, Qualitative research